Pengelompokkan Kabupaten/Kota Provinsi Jawa Timur Berdasarkan Indikator Kesejahteraan Rakyat Menggunakan Metode Elbow dan Algoritma K-Prototype - Mohamad Rivaldi Koni; Ismail Djakaria; Nisky Imansyah Yahya (Hasanuddin University, 2023)
People's welfare is the goal of the State of Indonesia which is contained in the official state document, namely the opening of the 1945 Constitution paragraph IV, this can be interpreted to enjoy an affluent life, free from poverty and is a human right for every citizen in Indonesia. The grouping process is carried out to see the level of people's welfare for each Regency/City in East Java. In this study, before grouping, the number of clusters was selected using the Elbow method. After that do the grouping with the K-Prototype Algorithm. Furthermore, using Kruskal Wallis and Chi-Square, the test was carried out to determine the variables that influence grouping. The results of the study obtained the 3 best clusters using the Elbow method, grouping with the K-Prototype Algorithm where cluster 1 consisted of 4 Regencies/Cities, Cluster 2 consisted of 18 Regencies/Cities and cluster 3 consisted of 16 Regencies/Cities. Furthermore, the results of Kruskal Wallis and Chi-Square get 4 influential variables in the grouping, the 4 variables are the Number of Poor Population, Expenditures Per Capita, Open Unemployment Rate and Sources of Water for Drinking.